Penerapan Sistem Rekrutmen untuk Meningkatkan Keterikatan Karyawan - Dematria Pringgabayu; Hendriady de Keizer (Jurnal Manajemen Maranatha, 2017)
High employee engagement can have a positive effect on the progress of a company's business, including one of them is an insurance company. One of the factors that can shape employee attachment, whether it increases employee engagement, even lowers it, is the existing recruitment system in the company concerned. When an employee is recruited, starting from the first call-up session, until the employee enters the first day of work, the employee must pass through a series of recruitment systems. This research is conducted with the intention to test and know the factors that can increase employee's attachment one of which consists of recruitment system, and also by using work environment as moderation variable. The results show that employee selection and job design have a direct influence in establishing employee engagement, while the new employee orientation will increase employee engagement if moderated or reinforced by the environmental factors in which they work, and has no direct effect on increasing employee engagement.Â Keywords: employee engagement; health insurance company ; recruitment system; work environment